2013
DOI: 10.1016/j.rmed.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of a neutrophil elastase inhibitor (AZD9668) in patients with bronchiectasis

Abstract: NCT00769119.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
119
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 31 publications
0
119
0
2
Order By: Relevance
“…Therefore, not surprisingly, therapeutic manipulation of elastase has been proposed in bronchiectasis. In a proof of concept study, Stockley and colleagues tested an oral NE inhibitor for 4 weeks in 38 patients with bronchiectasis (41). Although the primary outcome of a reduction in sputum neutrophils was not achieved, the study showed a clinically important and significant improvement in FEV 1 of 100 ml versus placebo, and a more than 4-point improvement in the SGRQ, which did not reach statistical significance (41).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, not surprisingly, therapeutic manipulation of elastase has been proposed in bronchiectasis. In a proof of concept study, Stockley and colleagues tested an oral NE inhibitor for 4 weeks in 38 patients with bronchiectasis (41). Although the primary outcome of a reduction in sputum neutrophils was not achieved, the study showed a clinically important and significant improvement in FEV 1 of 100 ml versus placebo, and a more than 4-point improvement in the SGRQ, which did not reach statistical significance (41).…”
Section: Discussionmentioning
confidence: 99%
“…Given the previously noted importance of neutrophil elastase in pathogenesis [104], this represents a promising therapeutic target. Phase II studies of oral neutrophil elastase inhibitors have been reported while others are ongoing [105]. Data show the ability to inhibit elastase activity but without clear clinical benefits yet.…”
Section: A Stepwise Approach To Treatmentmentioning
confidence: 99%
“…In the context of recent studies with other agents for the treatment of bronchiectasis, the reduction in sputum neutrophils observed in this study indicates some clinical potential for CXCR2 antagonism in the management of bronchiectasis [13,30,31,37,38]. Current treatment options such as long-term macrolide antibiotics and corticosteroids are either of limited effectiveness or have a number of potential drawbacks, such as development of bacterial resistance and adrenal suppression [13,30,31,38,39].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, CXCR2 antagonism may have additional beneficial effects on airway goblet cell hyperplasia and mucus production, independent of the modulation of neutrophil migration [15]. However, as with other novel approaches in development, larger studies of a longer duration with careful phenotyping of participants will be needed to determine the clinical utility of CXCR2 antagonism in bronchiectasis [37]. The concept that treatment responses to CXCR2 antagonism relate to the cause of neutrophilic airway inflammation is supported by a recent trial of another compound in patients with COPD showing an important reduction in exacerbation frequency in smokers but an increase in non-and ex-smokers [41].…”
Section: Discussionmentioning
confidence: 99%